Fikih Pluralisme (Titik Temu Agama-Agama dalam Bingkai Hukum Islam) - Moch. Bachrurrosyady Amrulloh (Akademika, 2020)
Not a few Muslim communities in Indonesia reject the concept of pluralism, even the MUI itself has issued a special fatwa on the prohibition of this understanding. They assume that pluralism is against Islam, because there is a tendency to equate Islam with other religions. Pluralism is also widely understood as a form of ideology that seeks to justify all religions. Thus, people can change religion as they wish at any time, like people change clothes. Contemporary era Indonesia also witnessed a polemic around this issue. Misunderstanding of the concept of pluralism has at some level created two poles of Islamic understanding between the pros and cons of this concept. Nahdlatul Ulama’ (NU) and Muhammadiyah were even divided internally in their communities. This article will examine through a review of Islamic jurisprudence (fiqh) related to the meaning and nature of pluralism. This research becomes relevant because in addition to the polemic that still exists in this concept, on the other hand the diverse social realities of Indonesian society, also requires an understanding that needs to prioritize tolerance and respect for differences.